Factors that Influence the Level of Teacher Job Satisfaction in the Era of Society 5.0 - Romy, Elly; Silalahi, Marto; Nkrumah, Ivy Kesewaa; Sudirman, Acai (LPPM Undiksha, 2024)
Low teacher job satisfaction will affect learning activities. This has an impact on educational goals needing to be achieved optimally. The main objective of this research is to analyze the influence of teacher certification, work environment, compensation, organizational culture, motivation, and organizational commitment on job satisfaction. The research design uses a quantitative causality approach. To obtain research data using documentation instruments and distributing questionnaires online. The research sample consisted of 215 respondents. The basis for determining the sample is oriented towards a non-probability sampling approach using a purposive sampling formula. Data analysis uses a Structural Equation Modeling (SEM) approach using the Partial Least Square (PLS) method. Based on the research results, it was found that the work environment, organizational culture and organizational commitment had a significant effect on job satisfaction. Further research results show that teacher certification, compensation, and motivation do not significantly affect job satisfaction. Representatives of teacher job satisfaction can be seen when there is encouragement for teacher certification, the condition of the work environment, the amount of compensation received, the implementation of organizational culture, encouragement of motivation and organizational commitment, which are carried out comprehensively for teachers. The implications of this research state the importance of a holistic approach to measuring teacher job satisfaction in Indonesia. It is essential to apply a holistic approach that considers all the factors mentioned simultaneously, as teacher job satisfaction is often the result of complex interactions between various factors.